1999
DOI: 10.1183/09031936.99.14511679
|View full text |Cite
|
Sign up to set email alerts
|

Methacholine-induced volume dependence of respiratory resistance in preschool children

Abstract: Enhanced negative volume dependence of airway resistance is associated with bronchoconstriction in tracheostomized paralysed open-chest animals. Significant upper airways responses may be associated with bronchoconstriction and could thereby alter the pattern of volume dependence in spontaneously breathing subjects. The aim of the study was to test whether volume dependence of respiratory resistance (Rrs) could be demonstrated in preschool children undergoing routine methacholine challenge.The volume dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…In calculating tidal fluctuation in resistance the authors used measurements at instants of zero flow, at end inspiration and end expiration, which allowed the volume dependent changes in resistance to be measured independently of any flow-related effects. Using a linear regression model, MARCHAL et al [17] have also demonstrated the volume dependence of resistance during tidal breathing at baseline and after methacholine challenge in children with airway hyperresponsiveness to methacholine.…”
Section: Discussionmentioning
confidence: 99%
“…In calculating tidal fluctuation in resistance the authors used measurements at instants of zero flow, at end inspiration and end expiration, which allowed the volume dependent changes in resistance to be measured independently of any flow-related effects. Using a linear regression model, MARCHAL et al [17] have also demonstrated the volume dependence of resistance during tidal breathing at baseline and after methacholine challenge in children with airway hyperresponsiveness to methacholine.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of glottic influences appears to be made feasible by controlling the variation of R~ and Xrs with respiratory phase MARCHAL et al, 1999). These monofrequency studies have assessed pre-school children during bronchoconstriction using Z~s,G.…”
Section: Recent Applications Of Fot In Paediatric Subjectsmentioning
confidence: 99%
“…The partitioning of Raw from tissue components is often of interest. Also, the potential to measure Zrs during sleep and artificial ventilation is of great value, and uncooperative pre-school children can also be assessed (LEBECQUE and STANESCU, 1997;JACKSON et al, 1996;STOCKS, 1996;MARCHAL et al, 1999;LOOS et al, 2000;DELACOURT et al, 2000).…”
Section: Clinical Aspects Of Impedance Measurementsmentioning
confidence: 99%
“…Rrs also changes with flow associated with turbulence and other effects and in anaesthetised children can change two-fold with a three-fold change in flow under isovolumetric conditions [38]. Agonists can modulate the volume dependence of Rrs [39,40], which may have contributed to the changes in Rrs and Rrs SD in asthma and with BD. However, the effects of a BD on median Rrs were similar in both groups and no changes were observed in tidal volume with BD or between asthma and controls.…”
Section: Variation In Rrsmentioning
confidence: 99%